2012
DOI: 10.1371/journal.pone.0041290
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Ventilator-Associated Pneumonia in Adults Randomized Clinical Trial: Comparison of 8 versus 15 Days of Antibiotic Treatment

Abstract: PurposeThe optimal treatment duration for ventilator-associated pneumonia is based on one study dealing with late-onset of the condition. Shortening the length of antibiotic treatment remains a major prevention factor for the emergence of multiresistant bacteria.ObjectiveTo demonstrate that 2 different antibiotic treatment durations (8 versus 15 days) are equivalent in terms of clinical cure for early-onset ventilator-associated pneumonia.MethodsRandomized, prospective, open, multicenter trial carried out from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 44 publications
2
88
1
4
Order By: Relevance
“…A subsequent study corroborated this finding and confirmed that using 15 versus 8 days of therapy led to no difference in mortality, ICU length of stay, and mechanical ventilation days [59]. However, the rate of secondary infection was higher in the shorter duration group (35.3 vs. 19.3 %, p = 0.01).…”
Section: Duration Of Treatment: Short Versus Longmentioning
confidence: 57%
“…A subsequent study corroborated this finding and confirmed that using 15 versus 8 days of therapy led to no difference in mortality, ICU length of stay, and mechanical ventilation days [59]. However, the rate of secondary infection was higher in the shorter duration group (35.3 vs. 19.3 %, p = 0.01).…”
Section: Duration Of Treatment: Short Versus Longmentioning
confidence: 57%
“…Th e role of inhaled antibiotics in the setting of failure of systemic antibiotics is unclear [1]. Th e usual duration of treatment for earlyonset VAP is 8 days and longer in the case of late-onset VAP or if MDR organisms are suspected or identifi ed [39]- [41].…”
Section: Treatmentmentioning
confidence: 99%
“…Cinq études répon-dant à ces critères ont été conduites en réanimation. Quatre études randomisées contrôlées, ayant comparé deux durées fixes de traitement, concernent les PAVM [224,[244][245][246] chez des patients adultes non immunodéprimés. Une cinquième, en néonatologie, concerne les bactériémies [247].…”
Section: Concernant La Procalcitonine (Pct)unclassified